2007
DOI: 10.1021/es062903j
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Arsenic During One-Year Incubations of Grey Aquifer Sands from Araihazar, Bangladesh

Abstract: Elevated As concentrations in shallow groundwater pose a major health threat in Bangladesh and similarly affected countries, yet there is little consensus on the mechanism of As release to groundwater or how it might be influenced by human activities. In this study, the rate of As release was measured directly with incubations lasting 11 months, using sediment and groundwater collected simultaneously in Bangladesh and maintained under anaerobic conditions throughout. Groundwater and grey sediment were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 44 publications
6
42
0
Order By: Relevance
“…Importantly, we believe that ancillary arsenic release has been obscured by the overprint of iron cycling. Laboratory and field experiments are showing that Fe and As release are decoupled (17,33,42) and that arsenic release occurs at a constant rate across various depositional environments (39). These observations are consistent with our novel mechanism that can occur under all redox conditions.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Importantly, we believe that ancillary arsenic release has been obscured by the overprint of iron cycling. Laboratory and field experiments are showing that Fe and As release are decoupled (17,33,42) and that arsenic release occurs at a constant rate across various depositional environments (39). These observations are consistent with our novel mechanism that can occur under all redox conditions.…”
supporting
confidence: 85%
“…Collecting microbially pristine sediment samples from Bangladesh aquifers is difficult and requires novel techniques (33, 41) compared to those traditionally utilized (16,29). Traditional drilling techniques are not available, and extensive work has been undertaken with the local drillers to obtain pristine samples that are not contaminated by drilling fluid (33,41). Briefly, during drilling a core or evacuated cylinder is lowered through the drill casing to collect sediment from below the casing.…”
mentioning
confidence: 99%
“…A variety of previous laboratory incubation studies [22][23][24][25] have found that the addition of labile organic carbon, or BDOC, mobilizes arsenic from Bengali aquifer sediments. Under a pond that loses ∼1.5 cm day −1 of water to the subsurface, sampling lysimeters show that dissolved arsenic increases with depth, although, at the deepest sampling point, arsenic has not reached the peak concentration measured in the aquifer (Fig.…”
Section: Reactivity Of Pond and Rice-field Rechargementioning
confidence: 99%
“…Both processes are to a great extent influenced by coexisting substances such as natural organic matters (NOM) and anions. It has been well documented that such substances may reduce arsenic adsorption and enhance arsenic transport through adsorption competition, complexation reactions, anion exchange and electrostatic repulsion (Barringer et al, 2011;Dias et al, 2009;Garcia-Sanchez et al, 2010;Garcia et al, 2007;Guo et al, 2014;He et al, 2010;Radloff et al, 2007;Reza et al, 2010;Serfes et al, 2003;Zheng et al, 2004). Thus, through such mechanisms, surfactant molecules may potentially influence arsenic adsorption and transport behavior in the environment.…”
Section: Introductionmentioning
confidence: 99%